Cocaine Causes Apoptotic Death in Rat Mesencephalon and Striatum Primary Cultures - Lepsch, Lucilia B.; Planeta, Cleopatra S. [UNESP]; Scavone, Critoforo (Hindawi Publishing Corporation, 2015)
To study cocaine's toxic effects in vitro, we have used primary mesencephalic and striatal cultures from rat embryonic brain. Treatment with cocaine causes a dramatic increase in DNA fragmentation in both primary cultures. The toxicity induced by cocaine was paralleled with a concomitant decrease in the microtubule associated protein 2 (MAP2) and/or neuronal nucleus protein (NeuN) staining. We also observed in both cultures that the cell death caused by cocaine was induced by an apoptotic mechanism, confirmed by TUNEL assay. Therefore, the present paper shows that cocaine causes apoptotic cell death and inhibition of the neurite prolongation in striatal and mesencephalic cell culture. These data suggest that if similar neuronal damage could be produced in the developing human brain, it could account for the qualitative or quantitative defects in neuronal pathways that cause a major handicap in brain function following prenatal exposure to cocaine.